Membandingkan Keberhasilan Pengembangan Food Estate Berbasis Reforma Agraria Di Desa Karangwangi, Mekarmukti dan Desa Sukawargi, Cisurupan, Kabupaten Garut - Pujiriyani, Dwi Wulan; Sugiasih, Sugiasih; Sutaryono, Sutaryono (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Food estate is a concept for developing food production which is carried out in an integrated manner and consists of agriculture, plantations and even animal husbandry on large areas of land. This article aims to examine the development of food estates based on agrarian reform which is being carried out in Java, especially in West Java. The material for this article was obtained through qualitative methods. The type of qualitative method used is multiple case studies. Data collection is divided into two, namely primary data collection techniques and secondary data. Secondary data was obtained through document study, while primary data was obtained through observation and interviews. The research results show that food estates in West Java, especially in the case of development in Sukawargi Village, have shown quite encouraging results. Farmers can streamline production costs while increasing production yields. The Agribusiness Operational Cooperation (KOA) partnership model allows farmers to gain increased income and also be free from the ties of middlemen. There has been a significant change where farmers, who previously continued to carry out traditional agricultural practices passed down from generation to generation, have changed to modern agriculture based on agricultural mechanization and innovation. Different things happen in Mekarwangi Village where basic problems related to agricultural supporting infrastructure are not yet available. This condition shows that Mekarwangi Village needs to be encouraged to fulfill the basic prerequisites for food estate development so that its success and sustainability can also be ensured.